Cardioprotection by H2S engages a cGMP-dependent protein kinase G/phospholamban pathway. (13th April 2015) - Bibli, Sofia-Iris; Andreadou, Ioanna; Chatzianastasiou, Athanasia; Tzimas, Christos; Sanoudou, Despina; Kranias, Evangelia; Brouckaert, Peter; Coletta, Ciro; Szabo, Csaba; Kremastinos, Dimitrios Th.; Iliodromitis, Efstathios K.; Papapetropoulos, Andreas
Abstract: Aims: H2 S is known to confer cardioprotection; however, the pathways mediating its effects in vivo remain incompletely understood. The purpose of the present study is to evaluate the contribution of cGMP-regulated pathways in the infarct-limiting effect of H2 S in vivo . Methods and results: Anaesthetized rabbits were subjected to myocardial ischaemia (I)/reperfusion (R), and infarct size was determined in control or H2 S-exposed groups. The H2 S donor sodium hydrosulfide (NaHS, an agent that generates H2 S) increased cardiac cGMP and reduced the infarct size. The cGMP-dependent protein kinase (PKG)-I inhibitor DT2 abrogated the protective effect of NaHS, whereas the control peptide TAT or l -nitroarginine methyl ester (l -NAME) did not alter the effect of NaHS. Moreover, the KATP channel inhibitor, glibenclamide, partially reversed the effects of NaHS, whereas inhibition of mitochondrial KATP did not modify the NaHS response. NaHS enhanced phosphorylation of phospholamban (PLN), in a PKG-dependent manner. To further investigate the role of PLN in H2 S-mediated cardioprotection, wild-type and PLN KO mice underwent I/R. NaHS did not exert cardioprotection in PLN KO mice. Unlike what was observed in rabbits, genetic or pharmacological inhibition of eNOS abolished the infarct-limiting effect of NaHS in mice. Conclusions: Our findings demonstrate (i) that administration of NaHS induces cardioprotection via a cGMP/PKG/PLN pathway and (ii) contribution of nitric oxide to the H2 S response is species-specific.